UNDP's engagement with the private sector, 1994-2011 - Razeq, Zarlasht M.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
An engaging explanation and unique analysis of the increased involvement of the private sector in one of the world's most influential development organizations, the United Nations Development Programme.
Keywords: Social sciences; Political science; Political theory; Political economy; International relations; Political philosophy; Economic policy; Social Sciences; Development Policy